PELAKSANAAN PERJANJIAN JUAL BELI BERAS OLEH PERUSAHAAN UMUM BADAN URUSAN LOGISTIK SUB DIVISI REGIONAL WILAYAH IV BANYUMAS DENGAN USAHA DAGANG AL FALAH - Nadia Yolanda; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Banyumas State Logistics Agency has implemented a Rice Sale and Purchase Agreement (PJB) with its partner, the Al Falah Trade Business. One form of negligence or broken promises in the implementation of the agreement that can be said to be detrimental to one party is the problem of default. The purpose of writing this thesis is to find out the factors that cause the occurrence of defaults carried out by the Al Falah Trade Business to the Banyumas Bulog Corporation and efforts to resolve the default in the implementation of the sale and purchase agreement carried out by the Banyumas Bulog Corporation with the Al Falah Trade Business.This research is a sociological or empirical research which is a type of research that uses the assumptions of the community in searching for facts that occur in the field to answer an existing problem. This research was carried out in the area of the General Enterprise of the Regional Logistics Agency, Regional IV, Banyumas. While the population and sample are parties related to the problem examined in this study, the source of the data used, primary data, secondary data, and tertiary data. Data collection techniques in this study were interviews and literature review.From the results of the research that the author did, it can be concluded, firstly the implementation of the sale and purchase agreement of rice between the Banyumas Bulog Public Corporation and its partners namely the Al Falah Trade Business stated in the form of an agreement referring to Presidential Instruction Number 5 of 2015 Concerning the Policy for Procurement of Grain or Rice and Rice Distribution by Government. In the rice sale and purchase agreement, there are problems of defaults carried out by the Al Falah Trade Business to the Banyumas Bulog Corporation, such as not delivering the rice supply within the period specified in the agreement, the delay in delivery of the rice in an additional period, the submitted rice is not in accordance with the quantity and quality stipulated in the agreement.Keywords : Rice Buy And Sell Agreement – Public Corporation Logistics Agency